Administration records: a largely untapped source of information for people who were in out-of-home care as children. Issue 1 (January 2018) - Rosser, Debra
Abstract : People who were in out-of-home care during their childhood or youth typically experience a range of problems when attempting to access the records created during that period of their lives. Records are frequently incomplete or no longer exist. This paper discusses some of the records-related issues that arise for survivors of childhood abuse in out-of-home care, and suggests that administration records may complement, supplement or be a replacement for client files. It describes the Restricted Archives Preservation (RAP) project funded by the Department of Communities (Child Protection and Family Support), Western Australia (formerly Department for Child Protection and Family Support (Western Australia) to make information from administration files more accessible for record-seekers.